ESTIMATION OF BIOMASS AND CARBON STORED IN VEGETATION AND SOIL IN THE ZONE OF INFLUENCE OF THE "PURISIMA" DAM, STATE OF GUANAJUATO, MEXICO - Fernando Carrillo-Anzures; Miguel Acosta-Mireles; Matilde Hernandez-Santiago; Ramiro Perez-Miranda; Martin Enrique Romero-Sanchez (Tropical and Subtropical Agroecosystems, 2023)
Background. Determining carbon in forest ecosystems is essential to estimate its influence on climate change mitigation. This study aimed to determine the carbon stored in the vegetation and soil of the Protected Natural Area of the "La Purísima" Dam and its influence zone in Guanajuato, Mexico. Methodology. The study area was classified according to its tree density as high, medium, low, and grassland. In each sampling site, tree species were identified, and total height and normal diameter were measured. In the shrub layer, crown diameter and height were measured. Species biomass was estimated using documented allometric equations, except for Myrtillocactus geometrizans (Mart. ex Pfeiff.) generated in this study. In the herbaceous layer, the percentage of coverage in the sites was considered, for which eight random samples of 0.25 m2 were taken. Carbon estimation stored in MgC ha-1 was obtained by multiplying the biomass by the factor 0.5. Carbon was measured in the soil by extracting 12 random samples at a depth of 20 cm. Results. In the 263.3 ha of the studied area, 16,627.7 MgC were estimated. The soil contributed 71.21%, the tree layer 24.6%, the shrub 1.86%, grass 0.75 and the herbaceous layer 1.57%. Implications. Even the species that develop in low deciduous forests have a reduced photosynthetic capacity; they significantly contribute to carbon stores. Conclusions. The difference in carbon storage varies according to the densities of the wood species; high densities have a greater amount of stored carbon in the aerial stratum and the soil. The carbon contributed by the grassland was barely perceptible.